Information infrastructure tools for bioterrorism preparedness. - Kun, L.G (IEEE Engineering in medicine and biology magazine)
As this paper was aimed at finding dual/multiple-use for the bioterrorism technology made possible by the large infusion of funds to the states and territories through the Center for Disease Control and Prevention request for proposals (CDC RFP), its six Focus Areas serve as vertical criteria on the figures that follow. The CDC RFP holds this prominent role, as the CDC was the agency tapped by DHHS to monitor the use of the funds and associated performance. The CDC's six Focus Areas (with Focus Area D, Laboratory Capacity - Chemical Agents apparently not funded this year) include: Focus Area A: Preparedness Planning and Readiness Assessment (including the National Pharmaceutical Stockpile (NPS) and associated response), Focus Area B: Surveillance and Epidemiology Capacity, Focus Area C: Laboratory Capacity iologic Agents, Focus Area E: Health Alert Network/Communications and Information Technology, Focus Area F: Communicating Health Risks and Health Information Dissemination, and Focus Area G: Education & Training. It should be noted that the importance of dual/multiple-use notwithstanding, the initial defined use of bioterrorism funds for each Focus Area (as outlined by the Congressional funding and latter elaborated on by DHHS and the CDC) should be met first. Thus, it is the goal of this article to accomplish both this and to find extensible systems capable of response to, and detection of, multiple emergency disasters or outbreak situations